Information Literacy, Young Learners and the Role of the Teacher Librarian. Issue 3 (3rd July 2019) - Laretive, Josephine
ABSTRACT: This paper examines information literacy and young learners in the context of the school environment. An overview of children's cognitive development and information processing, theories and models of information behaviour, and what defines information literacy is provided. Observation of young children's use of the Internet for information purposes and the role of the teacher librarian in providing teaching and learning sequences that guide young learners in information literacy skills is also profiled.